Saxifraga hirculus Linnaeus 1753 ... - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Saxifraga hirculus Linnaeus, Species Plantarum 1: 402. 1753. "Habitat in Suecia, Helvetia, Lapponia, Sibiria." RCN: 3158. Lectotype (Siplivinsky in Novosti Sist. Vyssh. Rast. 14: 99. 1977): Herb. Linn. No. 575.38 (LINN). Current name: Saxifraga hirculus L. (Saxifragaceae). Note: Webb (in Bot. J. Linn. Soc. 95: 264. 1987), evidently unaware of Siplivinsky’s earlier choice, independently designated the same collection as type. ... : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part S), pp. 806-877 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 821, DOI: 10.5281/zenodo.291971 ...